A modified human reliability analysis method for the estimation of human error probability in the offloading operations at oil terminals. Issue 3 (5th December 2020) - Zhang, Renyou; Tan, Henry; Afzal, Waheed
Abstract: Human error is a significant factor contributing to accidents during oil offloading at oil terminals. Fuzzy cognitive reliability and error analysis method (CREAM) is one of the applicable methods to estimate human error probability (HEP). However, the currently used fuzzy CREAM models have issues which weaken the quality of HEP results. Both the max‐min fuzzy CREAM and the weighted fuzzy CREAM neglect the compatibility degree of each activated fuzzy if‐then rule; besides, the max‐min fuzzy CREAM focuses only on the maximum and minimum input data and ignores their weights. Therefore, this paper presents a modified fuzzy CREAM to address all these issues to strengthen the quality of HEP estimation. The proposed approach employs fuzzy degree of each common performance condition (CPC), the weight of each CPC, and the compatibility degree of each activated fuzzy if‐then rule together to calculate HEP. The proposed approach is applied for HEP estimation in an oil offloading operation at the selected oil terminal. The final HEP value is estimated at 8.929 × 10 −3 . It is concluded that the proposed fuzzy CREAM model can provide more reliable results.